Assessment of Air Bengkulu (Indonesia) watershed based on agroecosystem landscape quality and sustainable land use plan - Muhammad Faiz Barchia; BAMBANG SULISTYO; KANANG S. HINDARTO; HERY SUHARTOYO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Barchia MF, Sulistyo B, Hindarto KS, Suhartoyo H. 2020. Assessment of Air Bengkulu (Indonesia) watershed based on agroecosystem landscape quality and sustainable land use plan. Biodiversitas 21: 5422-5430. This study purposes to assess agro-ecosystem landscape based on land quality values and current land use and assess agro-ecosystem matrices with agricultural conservation practices in Air Bengkulu Watershed conducted from August to December 2019. Spatial analysis used some map and Landsat 8 OLI satellite imagery and ArcGIS version 10.1. The analysis depicted spatial distribution of soil and land quality, land uses, agricultural landscape matrices, and sustainable agro-ecosystems. The assessments revealed soil quality covered Air Bengkulu Watershed categorized moderate 33.1% to good 14.4% suitable for sustainable agroecosystems while in marginal quality 38.9% mostly lying on the upstream. This unique landscape formed a land quality prone to degradation because of intensive agriculture for oil palm covering 60% and coffee plantation about 17%. Actually, only about 61.1% of the Air Bengkulu Watershed is categorized as moderate to good quality matrix of sustainable agroecosystems. Improper agricultural cultivation with monoculture system without implemented conservation practices drove landscape filled with degradation landscapes. With sustainable agro-ecosystem scenarios implementing physical conservation terraces and restored with multi-purposes tree species such as candlenut, kapok tree, betel nut, durian, good quality of the landscape matrix of 82% Air Bengkulu Watershed.